Activation Versus Inhibition of IGF1R: A Dual Role in Breast Tumorigenesis - Bulatowicz, Joseph J.; Wood, Teresa L. (Frontiers in Endocrinology, 2022)
Historically, the body of literature surrounding the insulin-like growth factor type 1 receptor (IGF1R) has described a largely pro-tumorigenic role in breast cancer cells and in several transgenic or xenograft mouse models. Interestingly, however, more recent evidence has emerged that suggests an additional, previously undescribed, tumor suppressive function for IGF1R in both human breast tumors and mammary oncogenesis in mice. These seemingly conflicting reports can be reconciled when considering what is currently known about IGF1R function in the context of tissue development and cancer as it relates to cellular growth, proliferation, and differentiation. In this mini review, we will summarize the currently existing data with a particular focus on mouse models that have been developed to study IGF1R function in development, tumorigenesis, and metastasis in vivo and propose hypotheses for how both the tumor-promoting and tumor-suppressing schools of thought regarding IGF1R in these histological contexts are compatible.